Hubungan Stres Kerja, Konflik dan Lingkungan Kerja Fisik Terhadap Prestasi Karyawan PT. Telesindo Shop Batam - Toto Cahya Praja; Firmansyah Kusasi; Iranita Iranita (Bahtera Inovasi, 2018)
In the business world today is growing rapidly this can be seen competition between companies.PT. Telesindo Shop as the official dealer of Telkomsel always improves the quality and quantity of the company.In this study reasearchers are interest in conducting research at PT. Telesindo Shop chapter Batam which aims to determine whether there is influence or how much influence the work stress, work conflict and physical work environment on employee performance. This study uses quantitative methods with data collection techniques through quentionnairies. Sample in this study were 30 people using full sample methods.The results of the study concluded that work stress, work conflict and physical environment partially have a positive and significant influence on employee performance. Meanwhile, simultaneously work stress, work conflict and work environment together have influences on employee performance at PT. Telesindo Shop chapter Batam. The most dominant variable is the physical environment. The results of this study imply that work stress, conflict and environment are things that need to be considered to improve employee performance to be better for the realization of company goals.